MODEL PENDIDIKAN KEWIRAUSAHAAN PEREMPUAN LOKAL DESA AOPA KECAMATAN ANGATA - Hasma Nur Jaya (Institut Pendidikan Tapanuli Selatan, 2020)
Entrepreneurship management education is important because the Aopa village community is a community that commonly has a high school education background or even has elementary school education. This study was conducted to find out the entrepreneurship management education model for local women and know the inhibiting and supporting factors of entrepreneurship management education for local women. The method used in this study was field research which used a multi-case study design. The data was collected using three techniques offered by Bogdan and Biklen, namely; 1) in-depth interviews 2) participant observation 3) documentation studies. It then was analysed, and the validity of the data was checked. This study concludes that the education model for local women in the Aopa village is a self-education development model in the form of entrepreneurship training in the Aopa village of Angata District.It emphasizes how to identify opportunities for entrepreneurship and manage knowledge as an entrepreneurial resource by applying management functions in its management. There are four inhibiting factors and three supporting factors in designing entrepreneurship education models for local women in the Aopa village.